Analisis Pengaruh Pembangunan Infrastruktur Daerah Terhadap Tingkat Kemiskinan Di Kabupaten Maluku Tenggara - Matdoan, Arsad; Ramly, Amin; Tamher, Etvin R.; Ingratubun, Muhammad R. A. (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to see and analyze the effect of Road, Education, Health and Telecommunication infrastructure development on the poverty rate in Southeast Maluku Regency. This research uses a quantitative approach with Multiple Linear Regression analysis methods and data processing using the Eviews application. This study used secondary data obtained from related agencies. The results of this study show that Road Infrastructure and Telecommunication Infrastructure have a negative and significant effect on regional poverty levels in Southeast Maluku Regency. This is evidenced by the results of the t-statistical test which shows a coefficient value of -4.126048 with a probability value of 0.0091 in Road Infrastructure and Telecommunication Infrastructure obtained t-statistical test results which show a coefficient value of -3985471 with a probability value of 0.0105. Meanwhile, Education Infrastructure and Health Infrastructure do not have a significant effect on the poverty rate in Southeast Maluku Regency. This is evidenced by the t-statistical test which shows a coefficient value of 1.044468 with a probability value of 0.3441 in Education Infrastructure and Health Infrastructure obtained t-statistical test results that m show a coefficient value of 0.7993 with a probability value of 0.0105.